Vitamin E-based Folic Acid Nanoemulsion: Formulation and Physical Evaluation for Oral Administration - Adi, Annis C.; Christanto, Christanto; Rachmawati, Heni; Adlia, Amirah (Pharmaceutical Nanotechnology, 2019)
Background: Folic acid is essential in many metabolic processes and DNA synthesis. Nevertheless, folic acid is not stable, pH-sensitive, and deteriorated upon light exposure. Objective: This work was aimed to improve folic acid stability within vitamin E-based nanoemulsion. Methods: The nanoemulsion was prepared with self-nanoemulsification method by mixing vitamin E oil, Tween 20, and PEG 400. A pseudoternary phase diagram was constructed with aqueous titration to determine the optimum ratio for the mixture. The globule size, pH and entrapment efficiency were included in the nanoemulsion characterizations. In addition, the influence of centrifugation, storage, and pH on physical and chemical stabilities of folic acid nanoemulsion was evaluated. Results: Optimum formula was obtained from vitamin E, Tween 20, and PEG 400 with the ratio of 1:11:1, and the folic acid amount was 8 mg. The size of folic acidloaded oil globule was 15.10 ± 1.51 nm, and the nanoemulsion pH was 6.24 ± 0.01. The nanoemulsion system was able to load the folic acid completely. Folic acid in nanoemulsion was stable after 14 days at room temperature, and it was more stable compared to folic acid in solution. In addition, the physical and chemical characteristics of folic acid in nanoemulsion was not affected by the simulated gastric condition. Conclusion: Hence, nanoemulsion is a promising strategy to enhance folic acid stability.
Keywords: nanoemulsion